Magma chamber dynamics in a silicic LIP revealed by quartz: The Mesoproterozoic Gawler Range Volcanics - Agangi, Andrea; McPhie, J.; Kamenetsky, V. (2011)
Silicic-dominated large igneous provinces (SLIP) represent vast amounts of magma (≥ 105 km3) erupted onto the Earth's surface or injected into the crust over short time spans, and are important components of the continental crust. The conditions of formation and evolution of these large magmatic provinces and their magma chambers are still poorly constrained. In this contribution, we examine cathodoluminescence textures and trace element (Al, Ti, Fe) zoning of quartz in a Mesoproterozoic SLIP, the Gawler Range Volcanics (GRV), South Australia. We describe intra-granular textures such as truncation of growth textures and reverse zoning (rimwards increase of Ti content). These characteristics of quartz, together with remelting of already crystallised portions of the magma chamber (felsic enclaves), suggest a complex history of crystallisation and resorption, and fluctuating magma temperature. Titanium-in-quartz geothermometry indicates that adjacent quartz zones record temperature variations (ΔT) up to 70 °C in volcanic units. We also report contrasting (non-correlatable) zoning patterns amongst quartz crystals, each indicating different crystallisation conditions. The juxtaposition of quartz crystals with contrasting zoning patterns is consistent with a dynamic regime (convection, stirring, overturning) of the GRV magma chamber. These results point to pulsating magmatic conditions, compatible with a non-linear evolution of the GRV magma chamber. Heat, necessary to explain both intra-granular and infra-granular textural variations, may have been provided in different pulses by underplating of mafic magma.